Peran Brand Ambassador dalam Penguatan Citra Pelayanan Umrah di Biro Hajar Aswad Surakarta - Saputra, Rizal Zeni (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2025)
This study is motivated by the increasing competition among umrah travel agencies, which demands effective communication strategies to build a positive public image. Hajar Aswad Mubaroq Surakarta employs brand ambassadors namely the guiding ustadz as key figures in enhancing pilgrims’ trust and satisfaction. The study aims to describe the contributions of brand ambassadors and the da’wah-based communication strategies used to shape a positive service image. A descriptive qualitative approach was applied, with data collected through in-depth interviews with guiding ustadz, agency staff, and pilgrims, as well as through observation and documentation. Data were analyzed deductively through processes of reduction, presentation, and conclusion drawing, and validated using source and method triangulation. The findings reveal that the guiding ustadz play a strategic role as brand ambassadors, serving not only as ritual guides but also as representatives of the agency’s values. Their credibility, experience, friendliness, and emotional closeness position them as influential figures capable of strengthening the agency’s image. The communication strategies employed include two-way communication, persuasive approaches, humorous delivery, and personal interaction. The role of brand ambassadors effectively enhances the agency’s reputation, increases public trust, and encourages pilgrim loyalty, as indicated by high repeat-order rates.